Single Agent Antihypertensive Therapy and Orthostatic Blood Pressure Behaviour in Older Adults Using Beat-to-Beat Measurements: The Irish Longitudinal Study on Ageing. - CANNEY, MARK; KENNY, ROSE; LITTLE, MARK (My University, 2016)
Background Impaired blood pressure (BP) stabilisation after standing, defined using beat-to-beat mea- surements, has been shown to predict important health outcomes. We aimed to define the relationship between individual classes of antihypertensive agent and BP stabilisation among hypertensive older adults. Methods Cross-sectional analysis from The Irish Longitudinal Study on Ageing, a cohort study of Irish adults aged 50 years and over. Beat-to-beat BP was recorded in participants undergo- ing an active stand test. We defined grade 1 hypertension according to European Society of Cardiology criteria (systolic BP [SBP] 140-159mmHg ± diastolic BP [DBP] 90-99mmHg). Outcomes were: (i) initial orthostatic hypotension (IOH) (SBP drop 40mmHg ± DBP drop 20mmHg within 15 seconds [s] of standing accompanied by symptoms); (ii) sustained OH (SBP drop 20mmHg ± DBP drop 10mmHg from 60 to 110s inclusive); (iii) impaired BP stabilisation (SBP drop 20mmHg ± DBP drop 10mmHg at any 10s interval during the test). Outcomes were assessed using multivariable-adjusted logistic regression. Results A total of 536 hypertensive participants were receiving monotherapy with a renin-angioten- sin-aldosterone-system inhibitor (n = 317, 59.1%), beta-blocker (n = 89, 16.6%), calcium channel blocker (n = 89, 16.6%) or diuretic (n = 41, 7.6%). A further 783 untreated partici- pants met criteria for grade 1 hypertension. Beta-blockers were associated with increased odds of initial OH (OR 2.05, 95% CI 1.31 – 3.21) and sustained OH (OR 3.36, 95% CI 1.87 – 6.03) versus untreated grade 1 hypertension.
PUBLISHED
Keywords: blood pressure (BP) stabilisation; blood pressure (BP) stabilisation; Ageing; ANTIHYPERTENSIVE AGENTS; OLDER ADULTS; ORTHOSTATIC HYPOTENSION